Does a monetary union require international fiscal policy co-ordination? - Devereux, Michael B. (Economic & Social Studies, 1991)
In the debate over the set up of a single European currency, one of the principal areas of concern has been the implication of a single currency for the behaviour of sovereign fiscal authorities, and the possible need to constrain this behaviour. The importance of this problem will clearly depend upon the degree of effective independence that a European Central Bank can establish. However, even with a Central Bank that is independent in the sense that it is not bound by mandate to purchase any national government debt, there will still remain a situation of strategic interaction between, many sovereign fIscal authorities and the Central Bank. What are the likely outcomes of this strategic interaction?
Keywords: Monetary union; Fiscal policy; European Central Bank